The effects of musical auditory stimulation on heart rate autonomic responses to driving: A prospective randomized case-control pilot study - Alves, Myrela Alene [UNESP]; Garner, David M. [UNESP]; do Amaral, Joice A.T.; Oliveira, Fernando R.; Valenti, Vitor E. [UNESP] (Elsevier, 2019)
Stress induced by driving has been revealed to increase the chances of cardiovascular complications and is involved or related to traffic accidents. In order to develop strategies to avoid health problems during driving we aimed to evaluate the acute effects of auditory stimulation with music on heart rate variability (HRV) during driving in congested urban traffic. This is a prospective cross-sectional randomized controlled pilot study conducted with five healthy women. Subjects were evaluated on two different random days, whose order of execution was established through a randomization process. In the music protocol the volunteers were exposed to music for the entire 20 min of traffic while in the control protocol the subjects performed the same procedures but were not exposed to any music. We noted that all Higuchi fractal dimension parameters except Kmax 10, Kmax 130 and Kmax 140 were reduced between pre-driving in the control protocol vs. driving in the control protocol. The same changes were noted between pre-driving in the music protocol vs. driving in the control protocol. In conclusion, musical auditory stimulation improved nonlinear HRV changes induced by driving.
Keywords: Autonomic nervous system; Cardiovascular physiology; Cardiovascular system; Hearing; Physiological; Stress